Pendampingan Pendidikan Lingkungan Hidup pada Siswa Sekolah Dasar - M. Amrul Khoiri; Fariz Satya Fardan; Azzahrah, Nabillah; Azharil Kalam; Azizah Putri Fahira; Angelina Novita Silaban; Dwi Arini; Gugun Paqta; Kevin Renaldi Listiawan; Muhammad Azmi; Syukri Syaputra (Program Studi Kehutanan, Universitas Khairun, 2024)
Environment is the space and everything in it, including all objects, forces, conditions, living creatures, humans, and their behavior that influence each other. Lack of concern and responsibility for the environment impacts pollution and natural disasters that can damage the environment. Environmental damage can be prevented with awareness of the environment instilled from an early age. Environmental education for elementary school students is expected to increase awareness and concern for the environment. The method used in this dedication is in the form of mentoring in environmental education, namely participatory action research (PAR). The target of this dedication is children who are still in elementary school in the Dusun Sungai Jermal, Kepenghuluan Teluk Piyai Pesisir, Kubu District, Rokan Hilir area. The dedication was carried out in SDN 014 Teluk Piyai Pesisir and SDN 016 Teluk Piyai Pesisir on August 3 and 10, 2024. The evaluation results show that students have a good understanding of various aspects of environmental education. The understanding criteria show their good knowledge of environmental concepts and elements, while an average score of 5 reflects their high awareness of the importance of environmental preservation. This dedication shows that students have a good understanding of environmental concepts and practical applications such as waste separation and tree planting, with an average score indicating that they not only understand the theory but can also apply it in their daily lives.